2005
DOI: 10.1074/jbc.m505294200
|View full text |Cite
|
Sign up to set email alerts
|

p300 Modulates ATF4 Stability and Transcriptional Activity Independently of Its Acetyltransferase Domain

Abstract: ATF4 plays a crucial role in the cellular response to stress and multiple stress responses pathways converge to the translational up-regulation of ATF4. ATF4 is a substrate of the SCF ␤TrCP ubiquitin ligase that binds to ␤TrCP through phosphorylation on a DSGXXXS motif. We show here that ATF4 stability is also modulated by the histone acetyltransferase p300, which induces ATF4 stabilization by inhibiting its ubiquitination. Despite p300 acetylates ATF4, we found that p300-mediated ATF4 stabilization is indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 38 publications
6
69
1
Order By: Relevance
“…As shown in Fig. 8A, in the absence of TFIIA␥ overexpression, ATF4 protein was rapidly degraded and almost undetectable on Western blot by 3 h after CHX addition, which is consistent with a previous study (51). However, overexpression of TFIIA␥ greatly delayed the degradation process with the levels of ATF4 protein only slightly reduced by 3 h after CHX addition.…”
Section: Silencing Of Tfiia␥ Markedly Reduces Levels Of Endogenous Ocsupporting
confidence: 79%
See 3 more Smart Citations
“…As shown in Fig. 8A, in the absence of TFIIA␥ overexpression, ATF4 protein was rapidly degraded and almost undetectable on Western blot by 3 h after CHX addition, which is consistent with a previous study (51). However, overexpression of TFIIA␥ greatly delayed the degradation process with the levels of ATF4 protein only slightly reduced by 3 h after CHX addition.…”
Section: Silencing Of Tfiia␥ Markedly Reduces Levels Of Endogenous Ocsupporting
confidence: 79%
“…Taken together, these results indicate that PKA is the major pathway mediating PTH activation of ATF4 in osteoblasts with PKC and MAPK/ERK pathways playing lesser roles in the PTH response. The concentrations of the inhibitors or activators used in this study are in the range reported to selectively affect the relevant pathways (33,(51)(52)(53). We found no evidence of toxicity; compounds did not reduce cell DNA or protein under the current condition (data not shown).…”
Section: Protein Kinase a (Pka) Is The Major Signaling Pathway Mediatmentioning
confidence: 66%
See 2 more Smart Citations
“…Phosphorylationdependent degradation of ATF4 is tightly modulated by the interactions with an E3 ubiquitin ligase-the SCFβTrCP (Skp1/ Cullin/F-box protein) complexes; however, the kinase(s) regulating stability of ATF4 has not been identified. 36,37 Further evidence that ATF4 is degraded by the UPS is provided by studies using inhibitors of the proteasome.…”
Section: Atf4 In Resistance To Anti-cancer Drugsmentioning
confidence: 99%